A Quasi‑Experimental Comparison of Problem‑Based Learning and Conventional Teaching Methods on the Mathematics Achievement of Tenth‑Grade High School Students - Ermahayu, Dwi Indah; Yuliastuti, Rita; Sulistyaningrum, Heny; Rahayu, Puji (Journal of Research in Vocational Education, 2026)
This study compares the effectiveness of the Problem Based Learning PBL model with conventional teaching methods in improving the mathematics learning outcomes of tenth grade high school students. A quasi-experimental design was employed, with two groups of 36 students each. The experimental group used the PBL model, while the control group followed conventional methods. Data was collected through tests and observations, with the results analyzed using the Mann Whitney test. The study concluded that the PBL model significantly improves student mathematics learning outcomes compared to conventional teaching methods.